The Rhythm of Life - Osuoha, Ngozi Olivia (Book collections on Project MUSE., 2019)
The Rhythm of Life is a record breaking book written in rhyme. It covers many facets of life, bent on the lessons, methods, and realities of life. Ngozi Olivia Osuoha is a poet, writer, thinker, and hymnist. She has published seventeen poetry books, including one co-written. She has featured in over sixty five international anthologies, and has also published over two hundred and fifty poems and articles in over twenty countries.